Benthic bioturbations weaken the stability of blue carbon storage - Huang Yingrong; Zhang Peng; Peng He-Bo; Pan Feng; Liu Yan; Wang Kai; Cai Yu; Wang Jianyu; Wang Zhenyan; Zheng Chunmiao; Li Hailong; He Ding; et al. (National Science Open)
Coastal ecosystems are known for their ability to sequester organic carbon (OC), termed “blue carbon”. The molecular composition of dissolved organic matter (DOM) can affect sediment OC content; however, the impact of benthic bioturbation on DOM properties and OC storage stability is not well understood. This study examined the effects of bioturbation by fiddler crabs on DOM molecular properties and OC storage stability along the Chinese coastline. These findings indicate that crab bioturbation enhanced the release of labile molecules by 59% on average. This increase is controlled by the coupling reactions of iron and manganese minerals, and is influenced by climatic gradients. Moreover, fiddler crab bioturbation diminishes the durability of blue carbon storage, with the most significant effects observed in mangrove forests, followed by bare mudflats, tidal creek banks, and saltmarshes. These results underscore the critical role of benthic bioturbation in global blue carbon budgets.